PENERAPAN MEDIA KARTU HURUF UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PESERTA DIDIK KELAS 3 DI UPT SD NEGERI 222 GRESIK - Cindy Lailatin Fitria (Yayasan Nusantara Hasana Berdikari, 2024)
Implementation of Letter Card Media to Improve Reading Skills of Grade 3 Students at UPT Sd Negeri 222 Gresik. Thesis, Elementary School Teacher Education Program. Faculty of Teacher Training and Education. Muhammadiyah University of Gresik (supervised by Mr. Ismail Marzuki M.Pd and Mr. Nanang Khoirul Umam, M.Pd). This study aims to describe the process of implementing and the quality of letter card media on the material of characteristics of living things for grade 3 elementary school students in the 2021-2022 academic year. The research model used in this application study is a qualitative model. The subjects of this study were grade 3 students of UPT SD Negeri 222 Gresik, totaling 23 students. The learning model used during this study was qualitative, which included interviews and observations. The data collection technique for this study was through observation and interviews. The observation results were obtained by 78% of 44% of students.